Frequent SLC35A2 brain mosaicism in mild malformation of cortical development with oligodendroglial hyperplasia in epilepsy (MOGHE) - Bonduelle, Thomas; Hartlieb, Till; Baldassari, Sara; Sim, Nam Suk; Kim, Se Hoon; Kang, Hoon Chul; Kobow, Katja; Coras, Roland; Chipaux, Mathilde; Dorfmüller, Georg; Adle-Biassette, Homa; Aronica, Eleonora; et al. (Acta Neuropathologica Communications, 2021)
Focal malformations of cortical development (MCD) are linked to somatic brain mutations occurring during neurodevelopment. Mild malformation of cortical development with oligodendroglial hyperplasia in epilepsy (MOGHE) is a newly recognized clinico-pathological entity associated with pediatric drug-resistant focal epilepsy, and amenable to neurosurgical treatment. MOGHE is histopathologically characterized by clusters of increased oligodendroglial cell densities, patchy zones of hypomyelination, and heterotopic neurons in the white matter. The molecular etiology of MOGHE remained unknown so far. We hypothesized a contribution of mosaic brain variants and performed deep targeted gene sequencing on 20 surgical MOGHE brain samples from a single-center cohort of pediatric patients. We identified somatic pathogenic SLC35A2 variants in 9/20 (45%) patients with mosaic rates ranging from 7 to 52%. SLC35A2 encodes a UDP-galactose transporter, previously implicated in other malformations of cortical development (MCD) and a rare type of congenital disorder of glycosylation. To further clarify the histological features of SLC35A2-brain tissues, we then collected 17 samples with pathogenic SLC35A2 variants from a multicenter cohort of MCD cases. Histopathological reassessment including anti-Olig2 staining confirmed a MOGHE diagnosis in all cases. Analysis by droplet digital PCR of pools of microdissected cells from one MOGHE tissue revealed a variant enrichment in clustered oligodendroglial cells and heterotopic neurons. Through an international consortium, we assembled an unprecedented series of 26 SLC35A2-MOGHE cases providing evidence that mosaic SLC35A2 variants, likely occurred in a neuroglial progenitor cell during brain development, are a genetic marker for MOGHE.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Brain mosaicism; Epilepsy; Focal cortical dysplasia; Glycosylation; Malformations of cortical development; SLC35A2 gene